ANALYSIS OF WORK ATTITUDES AND WORK DISCIPLINE ON WORK PRODUCTIVITY - Sutrisno Sutrisno; Karyono Karyono; Muhammad Sawir (SEAN Institute, 2023)
The goal of this study is to analyze and calculate the effect of work attitude and work discipline factors on work productivity. PT. Pos Indonesia Bandung City Branch was used as the population in this study, with a total sample of 49 personnel, utilizing a non-probability sampling technique or a saturated sample. The researchers employed a quantitative technique, as well as descriptive and associative methodologies. Multiple correlation analysis, multiple linear regression analysis, coefficient of determination test, partial hypothesis testing (t test), and the F test are all utilized in the analysis. According to the research findings, the work attitude variable has a significant positive effect on the work productivity variable, whereas the work discipline variable has a significant positive effect on the work productivity variable. According to the F test results, work attitude and work discipline variables both have a substantial influence on work production variables.